Management approaches for Industry 4.0 – the organizational culture perspective - Mohelska, Hana; Sokolova, Marcela (Technological and Economic Development of Economy, 2018)
The Industry 4.0 concept describes a decentralized production chain that extends from design to the supply chain, production, distribution as well as customer service. Cyber Physical Systems (CPS) employ software and internet-connected machines that communicate in real-time to reduce error rates and increase efficiency. The basis is the co-operation of separate control units that are capable of autonomous decision-making, managing the assigned technological unit and in particular becoming an independent and full member of comprehensive production units. The Industry 4.0 concept requires continuous innovation and education that not only depends on the peoples’ skills but also on organizational culture. Appropriate managerial approaches play a vital role in the development of organizational culture. Most studies discuss technical aspects, but do not pay attention to managerial approaches and organizational culture, which are a major factor influencing the success of this concept. The aim of the paper is to examine the level of organizational culture in the Czech Republic and to seek appropriate managerial approaches for the development of organizational culture that can support the environment for innovation in the organization and therefore facilitate the entrepreneurship in the Industry 4.0 concept. A partial goal will be, among other things, to identify the implications of Industry 4.0 for human resources. In order to determine organizational culture in organizations, a large study was carried out in the form of a questionnaire survey − the Czech translation of Wallach᾽s Questionnaire (1983). According to the findings, the respondents perceive the organizational culture in the organizations under review is more bureaucratic and supportive than innovative. In their view the signs of innovative culture are not so striking. It is necessary to change managerial approaches to support innovative solutions.